Evaluating the Effect of Digital Media and Coginitive Styles on Kanji Learning: An Experimental Study Using Tanoshiijapanese.com - Nia Setiawati; Muhamad Aldillah; Cut Erra Rismorlita (Chi e Journal of Japanese Learning and Teaching, 2025)
This study examines the effect of digital learning media and cognitive styles on kanji learning outcomes, focusing on the use of the tanoshiijapanese.com website as a learning platform. The research aims to determine how this website supports students with different cognitive styles—Field Dependent (FD) and Field Independent (FI)—in learning kanji. As online and blended learning continue to evolve, the integration of interactive web-based tools has become essential in language instruction, particularly for complex writing systems such as Japanese kanji. This study employed a one-group pretest–posttest experimental design involving students enrolled in a Kanji I course. Participants completed a pretest, underwent learning sessions using tanoshiijapanese.com, and then completed a posttest. Results indicated that both FD and FI learners experienced significant improvement after the intervention, confirming the positive impact of the digital platform on kanji acquisition. Furthermore, FD learners achieved slightly higher gains than FI learners, suggesting that the website’s guided and visually structured format aligns more closely with the cognitive tendencies of FD learners. These findings underscore the potential of web-based tools to enhance kanji instruction while addressing individual learning preferences.